Hubungan Pengetahuan, Sikap, Informasi dan Peran Guru dengan Personal Hygiene Remaja Putri pada Saat Menstruasi di MTsN 2 Aceh Besar Tahun 2022 - Fitriani Fitriani; Hermansyah Hermansyah; Anwar Ahmad (Yayasan Literasi Sains Indonesia, 2022)
Menstruation is a fundamental phenomenon among young women. Menstruation is associated with several misconceptions about personal hygiene practices during menstruation which can be detrimental to the health of adolescents. This study aims to determine the relationship between knowledge, attitudes, information and the role of the teacher with the personal hygiene of adolescent girls during menstruation at MTsN 2 Aceh Besar. This type of research is descriptive analytic with cross sectional design. The study was conducted on January 14 to 15, 2022. The population in this study were all 133 young women at MTsN 2 Aceh Besar class IX. The sample in this study were 60 people. Data was collected by distributing questionnaires. Analysis with univariate analysis and bivariate analysis using Chi-square test. The results showed that (33.3%) personal hygiene was in the poor category, (38.3) lacked knowledge, (25%) had a negative attitude, (31.5) had no information and (46.7%) the teacher's role was lacking. From the results of statistical analysis, it can be concluded that there is a relationship between knowledge (p value = 0.031), attitudes (p value = 0.004), information (p value = 0.002) and the role of teachers (p value = 0.005) with the personal hygiene of adolescent girls during menstruation in Indonesia. MTsN 2 Aceh Besar. It is hoped that health workers can provide health education to young women by providing counseling about reproductive health, especially about personal hygiene during menstruation.